Letter from Sybil - Ifoegbuna Ifeanyi (Literamed publications, 2000)
Ola and Yinka are married and blessed with a baby boy. Their marital life has been Characterised by fighting and quarrel because Yinka, Ola's wife does not run the home hygienically. This unhealthy environment attracts Wellington, a very intelligent rat, Beauty his wife and Sybil their daughter. The Olas have a very difficult task chasing away these rats because the rats are poised to foil their plans.
Keywords: Juvenile Fiction / Realistic / Unhealthy Environment